READINESS OF LISTED COMPANIES IN THE PREPARATION OF SOCIAL AND ENVIRONMENTAL RESPONSIBILITY REPORTS - Ririn Breliastiti; Temy Setiawan; Tiwi Herninta; Viana Ramadhanti (Jurnal Ekonomi, 2023)
The importance of disclosing sustainability issues in company reports is no longer an inevitable thing. Although it is still a voluntary matter, but the pressure of legitimacy is increasing amid the awareness of local and global stakeholders are starting to rise. Therefore, the company needs to make its disclosure in the annual report or a separate report called the sustainability report. This study seeks to map the readiness of companies listed on the Indonesia Stock Exchange in disclosing sustainability issues. This research is a descriptive qualitative research with 810 companies listed on the Indonesia Stock Exchange on December 31, 2022. The analysis technique used is content analysis technique. Sample observation data as many as 535 company data. The results show that 62% of companies disclose sustainability issues either in annual reports with separate sub-chapters or using sustainability reports. In addition, another 18% revealed but integrated in the discussion of the annual report. This study is important to see the readiness of companies in Indonesia in reporting sustainability issues that may later become mandatory like other countries.